TEACHING LISTENING THROUGH DLTA (DIRECTED LISTENING THINKING ACTIVITY) TO THE TENTH GRADE STUDENTS OF PGRI SENIOR HIGH SCHOOL 6 OF PALEMBANG - Yuspar Uzer (Universitas PGRI Palembang, 2015)
Abstract : Directed Listening –Thinking Activity (DLTA) is used in the building knowledge phase of a lesson, the part of a lesson in which students are inquiring to make meaning. In this activity, students listen to a story that is told or read to them and make predictions about what will come next. They are asked to confirm their prediction from time to time with information from the text, and to make new predictions. DLTA teaches students to listen or read actively, develop skill incomprehension of narratives, and use their awareness of genre and their understanding of plot structures to guide predictions. Based on the background above, the writer is interested to do a research entitled “Teaching Listening Through DLTA (Directed Listening Thinking Activity) to the tenth grade students of PGRI Senior High School 6 of Palembang”. The formulation of the problem of this study as follows :”Is it effective to teach listening through DLTA (Directed Listening Thinking Activity) to the Tenth Grade Students Of PGRI Senior High School 6 of Palembang?”. Based on the finding, it is found that the students’ average score in the pre-test was 5.39 and in the post test was 6.6. The significant level 5% (0.05) and degree of freedom (df) was 39 (40-1=39), the critical value of t-table for one tail test was 1.684 and the result of the obtained was 6.05, the result t-obtained of 6.05 exceed 1.684. It means that Ho (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. It indicates that teaching listening through DLTA (Directed Listening Thinking Activity) to the TenthGrade Students of PGRI Senior High School 6 of Palembang was effective. Keyword : Teaching, Listening Comprehension, DLTA (Directed Listening Thinking Activity)